Strategies for effective CBL implementation: from company selection to course evaluation - Vasquez-Lopez, Virgilio; Millan-Ramos, Moises; Maldonado-Carrillo, Refugio (Frontiers in Education, 2024)
In this study, we explore the key factors that educators must consider when designing challenges based on the Challenge-Based Learning (CBL) strategy, where the industrial sector serves as the educational partner. Building on our proposed definition of the CBL technique, we outline a methodology complete with practical suggestions to effectively tackle the challenges encountered during the strategy's implementation. The recommended steps involve choosing a training partner, establishing the company's role in the challenge, taking economic factors into account, and pinpointing crucial milestones in the course development, which includes recognizing the partner's involvement and significance in the course evaluation. Our proposal draws from the authors' experiences in applying this methodology within the context of an Industrial Automation course.